2007
DOI: 10.1124/mol.106.031823
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of MRP4 (ABCC4) in the Luminal Efflux of Ceftizoxime and Cefazolin in the Kidney

Abstract: The purpose of the present study was to investigate the role of multidrug resistance-associated protein 4 (MRP4) in the tubular secretion of cephalosporin antibiotics. Most of the injectable cephalosporins have an inhibitory effect on the ATP-dependent uptake of [ 3 H]dehydroepiandrosterone sulfate by membrane vesicles expressing hMRP4, whereas cephaloridine, cefsulodin, and cefepime do not. Aminocephalosporins have a weak inhibitory effect. Significant ATP-dependent transport of ceftizoxime (K m , 18 M), cefa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 29 publications
2
51
0
Order By: Relevance
“…For example, multidrug resistance-associated protein 4 (MRP4) was demonstrated to be responsible for the renal elimination of antiviral drugs, 6 diuretics 7 and cephalosporin antibiotics. 8 Human orthologs of the multidrug and toxin extrusion (MATE) family, members of which confer multidrug resistance on bacteria, were identified most recently, 9,10 and named MATE1 (SLC47A1) and MATE2-K (SLC47A2). Both transporters are expressed mainly in the renal brush border membranes, and are able to transport tetraethylammonium (TEA) utilizing an oppositely directed H + gradient as a driving force, 11 indicating that MATE1 and MATE2-K are H + /organic cation antiporters.…”
Section: Introductionmentioning
confidence: 99%
“…For example, multidrug resistance-associated protein 4 (MRP4) was demonstrated to be responsible for the renal elimination of antiviral drugs, 6 diuretics 7 and cephalosporin antibiotics. 8 Human orthologs of the multidrug and toxin extrusion (MATE) family, members of which confer multidrug resistance on bacteria, were identified most recently, 9,10 and named MATE1 (SLC47A1) and MATE2-K (SLC47A2). Both transporters are expressed mainly in the renal brush border membranes, and are able to transport tetraethylammonium (TEA) utilizing an oppositely directed H + gradient as a driving force, 11 indicating that MATE1 and MATE2-K are H + /organic cation antiporters.…”
Section: Introductionmentioning
confidence: 99%
“…MRP4 is an efflux transporter present on both on the apical membrane of renal proximal tubule cells as well as the surface of CD34 + stem cells and other bone marrow cells [8]. It has been shown that various β-lactam antibiotics are substrates of MRP4 using tandem mass spectrometry and in vitro studies of membrane vesicles expressing human MRP4 [10,11]. MRP4 also was demonstrated to be involved in the luminal efflux of ceftizoxime and cefazolin in the renal tubule of a mouse model; MRP4 knockout mice demonstrated higher renal concentrations of the cephalosporin antibiotics [11].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that various β-lactam antibiotics are substrates of MRP4 using tandem mass spectrometry and in vitro studies of membrane vesicles expressing human MRP4 [10,11]. MRP4 also was demonstrated to be involved in the luminal efflux of ceftizoxime and cefazolin in the renal tubule of a mouse model; MRP4 knockout mice demonstrated higher renal concentrations of the cephalosporin antibiotics [11]. Additionally, MRP4 knockout mice have also demonstrated bone marrow aplasia and enhanced hematopoietic toxicity with exposure to other studied drugs, such as thiopurine, suggesting that MRP4 may provide progenitor cell specific protection in its role as a surface cell transporter [14,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Moreover, this enzyme pumps out the diuretics furosemide and trichlorometazide 33 and the antibiotics cefazolin and cefotaxime. 34 The antitumor compounds methotrexate, 35 mitoxantrone, 36 topotecan, and imatinib, 37 the anthracyclines daunorubicin and doxorubicin, 38 as well as prazosin and nitrofurantoin, are substrates for BCRP/ABCG2. 30,39 The family of solute carrier (SLC) transporters is an important component of the organic anion efflux transport system of ECs.…”
Section: Bbb Functionmentioning
confidence: 99%